An Exploration of Pathological Gambling Among Diverse Populations - Perkins, Ayana N. (2011)
﻿This study used an ecological perspective to identify pathological gambling (PG) risk and protective factors, nonclinical resources, and prevention strategies based on the perceptions of Georgia stakeholders. With an ecological perspective, human behavior is perceived as an outcome of the interaction between the individual and various factors in their social environment. The ecological perspective is especially suitable for examining the higher PG prevalence among ethnic minority groups since these populations have been documented as encountering greater exposure to PG social and environmental risk factors (Smedley & Syme, 2000). To assess prevention needs, data were obtained from a 2008 needs assessment where diverse perspectives were collected through semi structured focus groups and interviews. A qualitative approach was used to address the study's aims. Grounded theory was used to guide the data analysis. Findings indicated that community perceptions of risk and protective factors, nonclinical resources, and prevention strategies were present at multiple levels of analyses. Furthermore, data trends also indicated that charitable gambling and other social norms should be considered in prevention